The effects of psychiatric and “biological” labels on lay sentencing and punishment decisions - Berryessa, Colleen M. (Journal of experimental criminology, 2018)
This research, using focal concerns perspective on sentencing, examines how and why psychiatric labels, and having diagnoses biologically “labeled,” affect sentencing beliefs. Dimensions of public stigma toward psychiatric illnesses are hypothesized to mediate sentencing views.